2004
DOI: 10.1016/j.ijgo.2004.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of a quality of care approach for improving emergency obstetric care in rural hospitals in Nepal

Abstract: We describe the iterative process of developing a locally-appropriate quality of care approach and its role in emergency obstetric care (EmOC) programming in Nepal. We describe the context of maternal health issues in Nepal, the rationale for developing a quality of care approach within a model to improve EmOC, and outline the outcomes and catalytic effects of the process. The lessons learned during the development of this approach are detailed. The program developed and implemented a quality of care approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…For improving and maintaining the quality, highly motivated staff with team work, collaborative activities with community, improved overall functioning of the health facilities, community awareness and positive perception towards providers are the inevitable aspects of emergency obstetric care. [23][24][25] An inter-countries cross-sectional study on global patterns of utilization of emergency obstetric care revealed that the comprehensive emergency obstetric care facilities are usually available to meet the recommended minimum number for the size of the population. Basic emergency obstetric care facilities are consistently not available in sufficient numbers both in countries with high and moderate levels of maternal mortality.…”
Section: 22mentioning
confidence: 99%
“…For improving and maintaining the quality, highly motivated staff with team work, collaborative activities with community, improved overall functioning of the health facilities, community awareness and positive perception towards providers are the inevitable aspects of emergency obstetric care. [23][24][25] An inter-countries cross-sectional study on global patterns of utilization of emergency obstetric care revealed that the comprehensive emergency obstetric care facilities are usually available to meet the recommended minimum number for the size of the population. Basic emergency obstetric care facilities are consistently not available in sufficient numbers both in countries with high and moderate levels of maternal mortality.…”
Section: 22mentioning
confidence: 99%
“…Despite efforts in Nepal to increase rates of institutional birth, 35 % of births nation-wide take place in a medical facility and in the impoverished Far-Western Development Region where this study takes place, that percentage is only 29 %. In Nepal, only 5 % of the estimated need for emergency obstetric care is met, and only 0.7 % of births are by cesarean section compared to the United Nations target of 5–15 % [5]. …”
Section: Introductionmentioning
confidence: 99%
“…The quality factors that are pertinent to public hospital clients include attitude, interpersonal and technical skills of service personnel [34]. Health facilities in Nepal are often understaffed with poor infrastructure, equipment and management [35,36]. An assessment of quality of care in midwifery and emergency obstetric care services in Nepal found major shortfalls [37].…”
Section: Introductionmentioning
confidence: 99%